Computational study on the low velocity impact (LVI) of laminated composites with panel size effects. (15th February 2023) - Lin, Shiyao; Ranatunga, Vipul; Waas, Anthony M.
Abstract: A computational study of the low velocity impact (LVI) responses and damage of IM7/977-3 composite laminates with various geometry parameters is presented in this paper. The in-plane sizes of the laminates are 152.4 mm × 101.6 mm, 177.8 mm × 177.8 mm, and 330.2 mm × 330.2 mm. The two panel thicknesses are 24-ply (3.1 mm) and 48-ply (6.2 mm). The two panel layups are [45/−45/0/90/0/0]ns and [45/0/−45/90]ns . Detailed experimental results have been reported in Lin et al. (2022). Two versions of Enhanced Schapery Theory with inelasticity (EST-InELA) implemented with 2D plane stress states and 3D stress states are applied to predict the LVI responses and damage. It is found that the EST models are able to predict most of the LVI-induced damage features accurately and the thickness-to-length/width ratio is identified as the most important geometric factor affecting the LVI responses and damage. Comparing the numerical results, 2D EST-InELA is more accurate in predicting the LVI-induced damage while 3D EST-InELA performs better in predicting the impact energy absorption. In addition, 2D EST-InELA is significantly more efficient than 3D EST-InELA. Recommendations for model applications are given towards the end of this paper. The results presented here capture the experimental results (Lin et al., 2022) with respect to panel size effects suggesting revisions to existing standards (ASTM-D7136, 2005).